(untitled) (Aporte Santiaguino, 2025)
Present and future water security face great challenges, due to the decrease in predicted rainfall due to the effects of climate variability and change, which is undoubtedly the greatest environmental challenge facing people around the world. The objective of this article was to explore scientific literature produced for an updated open access review, in the last 10 years on water security for future scenarios, using the WEAP (Water Planning and Evaluation System) as modeling software. The methodological procedure was the systematic review, using the logical operator AND with terms, “climate change”, “water safety” and “WEAP” in the databases Scopus, Scielo, ScienseDirect, Proquest and Redalyc. The results identify that at least they existed in Scopus (21), Scielo (15), ScienseDirect (20), Proquest (12) and Redalyc (10) that evidence the evaluation of present and future water security under anthropogenic climate changes using the model WEAP. It is concluded that, in the last 10 years, there has been a growing interest in studying climate change and future water security, and the literature emphasizes the importance of promoting research in undergraduate and graduate environments at universities to prevent future water crises.